“Advogado de bandido”: uma investigação acerca dos efeitos das representações sociais sobre a autoimagem de advogados criminalistas em Maceió - Acioli, Diogo José Palmeira (2020)
Social representations are forms that society uses to categorize phenomena and people, according to the attributes it considers likeable or not. Among these social representations, the image formed about criminal lawyers is negative. Although the Brazilian Federal Constitution establishes as a principle the right to full defense of people accused in criminal proceedings, defense which is done by a lawyer, there are not rare occasions when this professional is represented in a similar way to the client who defends, becoming popular terms like “bandit's lawyer” or “devil's advocate”, to refer to criminal attorneys. This dissertation intends to analyze how criminal lawyers who work in the city of Maceió, faced with negative social representations about their profession, build their self-image. For that, we mobilized the concepts of social representations, in authors such as Durkheim, Saussure and Strauss; stigma, in Goffman; and self and internal conversations, in Archer. The research methodology consisted of analysis of semi-structured interviews with seventeen criminal lawyers who work in the city of Maceió, in order to understand the universe of these professionals and verify how they build their self-image. Research has shown that criminal lawyers in Maceió perceive the negative social representations that exist against them in conduits that occur in both professional and extra-professional fields. However, they also develop reaction strategies against these behaviors and, in their life trajectories, create self-images distinct from the negative image established by society.